A taxonomic revision of order Pilisuctorida (Ciliophora, Apostomatia) with keys to the subordinate taxa - Dovgal, Igor; Mayén-Estrada, Rosaura (Zootaxa, 2015)
The article is to present a review of the taxonomic literature of pilisuctorid ciliates and new data from samples taken in Ukraine and Mexico. In order to contribute to the knowledge of this specialised ciliate group, the present article contains the general characteristics of order Pilisuctorida members, information on morphology and life cycles of all its representatives and some own data on distribution of three species of genus Conidophrys in Ukraine and Mexico. The taxonomic composition of this order, and diagnoses of all taxa are also included, as well the keys to the taxa.